Trends, Frameworks, and Reference Models in Public Sector Enterprise Architecture: A Systematic Review - Amanda Ghaisani; Dencaswo Purnomo; Dana Indra Sensuse; Sofian Lusa; Nurcholis Ramlan (Dinasti Research, 2026)
Global Trends and Reference Models in Public Sector Enterprise Architecture: A Systematic Review” examines enterprise architecture implementation in the public sector across countries. Enterprise architecture is increasingly used as a strategic instrument to support digital transformation and interoperability, yet existing studies remain fragmented and lack cross-country synthesis. This study aims to identify global trends, reference models, best practices, and challenges in public sector enterprise architecture implementation. The method used is a systematic literature review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses protocol, analyzing 23 peer-reviewed studies published between 2020 and 2025. The results show that The Open Group Architecture Framework (TOGAF) is the most frequently adopted framework and often becomes the basis for localized national models. This study identifies 15 reference models classified into national-level, domain-specific, regional government, and organizational agile models. Successful implementation is influenced by government commitment, inter-agency collaboration, and alignment with digital transformation strategies. The study concludes that enterprise architecture plays both strategic and technical roles in strengthening public governance. For public sector policymakers, the findings indicate that EA initiatives should be supported by clear governance mandates, cross-agency coordination mechanisms, and contextual adaptation of global frameworks to national priorities and institutional capacity.